Absorption of Islamic Law in National Law: Analysis of Law No. 1 of 1974 and KHI on Marriage - Habibi Siregar, Awaluddin; Yamamah, Ansari; Harahap, Arifuddin Muda (JURNAL AKTA, 2025)
The absorption of Islamic law into national law in Indonesia is the result of a compromise between sharia principles and the prevailing positive legal system. One form of this is Law No. 1 of 1974 concerning Marriage and the Compilation of Islamic Law (KHI), which regulates the legal aspects of marriage for Muslims. However, the implementation of these two regulations in various regions show variations, especially in determining the rights and obligations of husband and wife, including in terms of joint property. Cultural diversity and different legal interpretations often affect the application of this law, so an in-depth analysis is needed regarding the extent to which Islamic law has been absorbed into national law. This study aims to examine the implementation of Law No. 1 of 1974 and KHI in the context of Islamic marriage law, with a focus on the dynamics of the application of joint property. This study uses a qualitative method with a statute approach, a case approach, a comparative approach, and a conceptual approach. The results of the study show that although Islamic law has been accommodated in the national legal system, its application still faces challenges, especially related to differences in interpretation by judges and the community in judicial practice. In addition, social and cultural factors also influence the implementation of provisions regarding joint property in marriage. In conclusion, although Law No. 1 of 1974 and the KHI have adopted the principles of Islamic law, harmonization and uniformity of application are still challenges that need further attention to create better legal certainty.